The application of UASB reactor in meat industry wastewater treatment = Zastosowanie reaktora UASB do oczyszczania ścieków z zakładów mięsnych - Kwarciak-Kozłowska, Anna; Bohdziewicz, Jolanta; Mielczarek, Karolina; Krzywicka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The meat industry is a branch of the food sector, which significantly affects the degradation of the environment. Consuming large amounts of water consequently produces significant quantities of water which are characterised by a high organic content and high concentration of suspended solids, inorganic salts and nutrients.
Keywords: oczyszczanie ścieków z zakładów mięsnych; biogaz; reaktor UASB; meat industry wastewater; hydraulic retention time; biogas; reactor UASB